Family planning counseling and its associations with modern contraceptive use, initiation, and continuation in rural Uttar Pradesh, India - Nabamallika Dehingia; Anvita Dixit; Sarah Averbach; Vikas Choudhry; Arnab Dey; Dharmendra Chandurkar; Priya Nanda; Jay G. Silverman; Anita Raj (BMC, 2019)
Abstract Background We examine the association between the quality of family planning (FP) counseling received in past 24 months, and current modern contraceptive use, initiation, and continuation, among a sample of women in rural Uttar Pradesh, India. Methods This study included data from a longitudinal study with two rounds of representative household survey (2014 and 2016), with currently married women of age 15-49 years; the analysis excluded women who were already using a permanent method of contraceptive during the first round of survey and who reported discontinuation because they wanted to be pregnant (N = 1398). We measured quality of FP counseling using four items on whether women were informed of advantages and disadvantages of different methods, were told of method(s) that are appropriate for them, whether their questions were answered, and whether they perceived the counseling to be helpful. Positive responses to every item was categorized as higher quality counseling, vs lower quality counseling for positive response to less than four items. Outcome variables included modern contraceptive use during the second round of survey, and a variable categorizing women based on their contraceptive use behavior during the two rounds: continued-users, new-users, discontinued-users, and non-users. Results Around 22% had received any FP counseling; only 4% received higher-quality counseling. Those who received lower-quality FP counseling had 2.42x the odds of reporting current use of any modern contraceptive method (95% CI: 1.56-3.76), and those who received higher quality FP counseling at 4.14x the odds of reporting modern contraceptive use (95% CI: 1.72-9.99), as compared to women reporting no FP counseling. Women receiving higher-quality counseling also had higher likelihood of continued use (ARRR 5.93; 95% CI: 1.97-17.83), as well as new use or initiation (ARRR: 4.2; 95% CI: 1.44-12.35) of modern contraceptives. Receipt of lower-quality counseling also showed statistically significant associations with continued and new use of modern contraceptives, but the effect sizes were smaller than those for higher-quality counseling. Conclusions Findings suggest the value of FP counseling. With a patient-centered approach to counseling, continued use of modern contraceptives can be supported among married women of reproductive age. Unfortunately, FP counseling, particularly higher-quality FP counseling remains rare.